The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1177/0269216306070236
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pilot study of symptoms and quality of life in cancer patients and patients with end stage renal disease

Abstract: Patients with advanced renal failure experience a symptom burden and impairment of quality of life similar to that of patients with terminal malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 27 publications
(16 reference statements)
3
112
0
2
Order By: Relevance
“…The baseline characteristics of the remaining 63 patients are displayed in Table 1 and results of the GFI in Supplementary Table 2. Median age of included patients was 75 years (range 66-92) and 35% were women; 65% of patients were married, 27% was widower and 8% was unmarried. Median Charlson comorbidity index was 1 (range 0-6) and patients used a median of eight types of prescription medications (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Median eGFR at inclusion was 16 mL/min (range 5-34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline characteristics of the remaining 63 patients are displayed in Table 1 and results of the GFI in Supplementary Table 2. Median age of included patients was 75 years (range 66-92) and 35% were women; 65% of patients were married, 27% was widower and 8% was unmarried. Median Charlson comorbidity index was 1 (range 0-6) and patients used a median of eight types of prescription medications (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Median eGFR at inclusion was 16 mL/min (range 5-34).…”
Section: Resultsmentioning
confidence: 99%
“…16,17 As patients with advanced renal failure experience a symptom burden and impairment of quality of life similar to that of patients with terminal malignancy, such tools could perhaps also be used to screen for potentially frail elderly among geriatric ESRD patients. 18 In this study, we aimed to assess whether the GFI can be used to distinguish fit older ESRD patients, likely able to tolerate and benefit from dialysis, from frail older patients who need further evaluation with a geriatrician's comprehensive assessment in a daily nephrology outpatient setting. Secondly, we compared the results of the GFI, respectively the nephrologists' evaluation with the geriatrician's assessment with regard to different geriatric domains.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of symptoms for dialysis patients and those with advanced chronic kidney disease (CKD) who choose conservative care (i.e., no dialysis) is high (2), with the number and severity of symptoms (such as pain, nausea, anorexia, shortness of breath, insomnia, anxiety, and depression) rivaling those of many cancer patients (3)(4)(5)). An increasing number of patients are dying after withdrawal of dialysis (10% to 15% in 1990; 20% in 2004) (1), representing the second leading cause of death after cardiovascular disease.…”
mentioning
confidence: 99%
“…This finding differs from previous studies that showed no difference in the symptom burden between patients who die from cancer compared with patients who die from other causes. 8,14,39 Our finding may be because only oncology patients with symptoms are admitted for end-of-life care, whereas patients with fewer symptoms remain at home.…”
Section: Discussionmentioning
confidence: 86%